Configuring Citrix MetaFrame XP for Windows including future release 1 - Broomes, Chris (Rockland, Mass. : Syngress Media ; London : International Thomson, 2002)
Syngress's best-selling Citrix MetaFrame author to delivers world class support for this new product As the newest member of the Citrix MetaFrame product family, Citrix MetaFrame XP and recent add-on Feature Release 1 is making a slash in the IT community. Configuring Citrix MetaFrame XP for Windows offers system administrators and network engineers an in-depth look at configuring, optimizing, implementing and troubleshooting their Windows applications deployed using Citrix MetaFrame XP. Real-world examples and step-by-step exercises will help system administrators maxinise the capabilities of this revolutionary product from Citrix. The only book to-date to provide comprehensive coverage of the eagerly awaited Feature Release 1 add-on Citrix MetaFrame is a rapidly growing technology; as companies adopt thin-client technology, the number of Certified Citrix Administrators (CCAs) is set to skyrocket Unrivalled web based support at solutions@syngress.com.
Clients and Digital Independence -- Farming MetaFrame XP Servers -- Routing and Remote Access -- Designing the -- Client Solution -- Installing Citrix MetaFrame XP -- Connecting -- Clients -- Configuring the Server -- Citrix MetaFrame XP Management -- Installing and Publishing Applications -- Security and Load Management -- Extending Citrix MetaFrame XP Over the Internet -- Printing -- Wireless and Mobile Solutions -- Building a Portal -- Monitoring and Maintenance.
Includes index.
Keywords: Citrix MetaFrame; Client/server computing; Citrix MetaFrame (Computer file); Electronic books